The effect of the COVID-19 epidemic on Moroccan sectoral indices: The entropy approach - Fadwa Bouhlal; Moulay Brahim Sedra (Investment Management & Financial Innovations, 2022)
The current study investigates the impact of the Coronavirus 2019 (COVID-19) pandemic on the volatility of Moroccan stock market sectoral indices. Shannon entropy with multiple estimators and Rényi entropy for different scales were calculated from February 1, 2019 to May 1, 2022, to measure volatility in the Banking, Oil and Gas, Construction and Building Materials, Beverage, Food Producers and Processors, Distributors, and Mining sector’s indices. In this regard, this study uses three periods to quantify the uncertainty in Moroccan sectoral indices before, during, and after the first year of the COVID-19 pandemic in Morocco. The empirical results from Shannon and Rényi entropies indicated higher volatility during the COVID-19 pandemic for all sectoral indices except Oil and Gas. However, the consumer staples sectors have shown a form of resilience compared to other sectors. Indeed, the impact of COVID-19 on the consumer staples sectoral indices’ volatilities was negligible compared to other sectors. In addition, investing in a portfolio composed of Mining or Construction and Building Materials stocks was risky due to the increased volatility before and during the epidemic. However, after the COVID-19 pandemic, the entropy level corresponding to all sectors has rearranged except the Beverage sector, which kept the lowest entropy during the three periods. Thus, it seems that the Beverage sector was a safe investment for the three periods. The findings are crucial for governments, businesses, private and public authorities, and investors to create recovery action plans for sensitive sectors and give investors trust to make smarter investment decisions.